Generation and characterization of a mitotane-resistant adrenocortical cell line. Issue 2 (February 2020) - Seidel, Eric; Walenda, Gudrun; Messerschmidt, Clemens; Obermayer, Benedikt; Peitzsch, Mirko; Wallace, Paal; Bahethi, Rohini; Yoo, Taekyeong; Choi, Murim; Schrade, Petra; Bachmann, Sebastian; Liebisch, Gerhard; et al.
Abstract : Mitotane is the only drug approved for the therapy of adrenocortical carcinoma (ACC). Its clinical use is limited by the occurrence of relapse during therapy. To investigate the underlying mechanisms in vitro, we here generated mitotane-resistant cell lines. After long-term pulsed treatment of HAC-15 human adrenocortical carcinoma cells with 70 µM mitotane, we isolated monoclonal cell populations of treated cells and controls and assessed their respective mitotane sensitivities by MTT assay. We performed exome sequencing and electron microscopy, conducted gene expression microarray analysis and determined intracellular lipid concentrations in the presence and absence of mitotane. Clonal cell lines established after pulsed treatment were resistant to mitotane (IC50 of 102.2 ± 7.3 µM ( n = 12) vs 39.4 ± 6.2 µM ( n = 6) in controls (biological replicates, mean ± s.d., P = 0.0001)). Unlike nonresistant clones, resistant clones maintained normal mitochondrial and nucleolar morphology during mitotane treatment. Resistant clones largely shared structural and single nucleotide variants, suggesting a common cell of origin. Resistance depended, in part, on extracellular lipoproteins and was associated with alterations in intracellular lipid homeostasis, including levels of free cholesterol, as well as decreased steroid production. By gene expression analysis, resistant cells showed profound alterations in pathways including steroid metabolism and transport, apoptosis, cell growth and Wnt signaling. These studies establish an in vitro model of mitotane resistance in ACC and point to underlying molecular mechanisms. They may enable future studies to overcome resistance in vitro and improve ACC treatment in vivo .